The psychologizing of modernity : art, architecture, and history - Jarzombek, Mark. (Cambridge : Cambridge University Press, 2010)
- A prolegomenon to critical historiography ##- Introduction: art psychology, The elusive discipline ##- 1. The psychologizing of modernity: initial soundings ##- 2. The body ethos ##- 3. The vitalist ethos ##- 4. The social ethos ##- 5. The literary ethos ##- 6. Theory activism ##- Conclusion: the disciplinary dialectics of art and architecture's intellectual history
Originally published: 2000.
Includes bibliographical references and index.
boek